Optimization of the slow neutron detector array in the thermal neutron backscattering technique (2017)
Abstract: In Colombia, after decades of conflict, many geographical areas are believed to be contaminated by antipersonnel mines (MAP), Improvised Explosive Devices (IED) and other explosive ordnance. Mines laid by non-state armed groups are found around schools, houses and roads in rural areas. In some cases only the mined area is established however the exactly location of mines is unknown, this situation generates a latent threat to the civilian population. One of the nuclear techniques that are being investigated in different countries in the field of explosives detection and demining is the Thermal Neutron Backscattering Technique (TNBT). The TNBT is based on the fact that the buried target is Hydrogen-rich and therefore if it is in a media with different Hydrogen content and it is exposed to a fast neutron source, the number of backscattered thermal neutrons produced by the moderation process will give us a signal from which we can infer the presence of the Hydrogen-rich target. The TNBT has been used in controlled conditions to locate buried hydrogen-rich objects using a Cf-252 fast neutron source and two He-3 neutron detector arrays, also in different types of soil (sand and farming soil). The results of experiments are presented with the purpose of showing different possibilities of the detector arrays location, number of detectors per array, dependence with different soils and the best performance in the data analysis.